Does Audit Committee Constraint Discretionary Accruals in MESDAQ Listed Companies? - Yusof, Mohd. Atef Md (Asian Accounting and Auditing Advancement, 2012)
The role and responsibility of the audit committee toward credible financial reporting are still much the same, but the issue of selecting appropriate people with the right mind is often challenged. The usual tripartite, namely independence, diligence, and knowledge of the audit committee is further refined in the recently revised Malaysian Code of Corporate Governance 2007. The study examines the determinants of discretionary accruals in MESDAQ companies. The central issues are the key aspects of the audit committee, namely independence, expertise, and diligence including the issue of former senior auditors and audit alumni on the audit committee and its effect on discretionary accruals. Based on OLS regression on cross-sectional data of 2007, the results suggest that audit committees with a higher proportion of financial expertise (former senior auditor or former CFO) and more diligent audit committees are significant for the said purpose. As such, it is argued that an audit committee with a higher proportion of financial experts would lead to credible financial reporting. However, audit committees with the former senior auditor and audit alumni are associated with larger discretionary accruals. In addition, the total independent audit committee is positively associated with larger discretionary accruals which lead to possible limited access to pertinent financial information compared to the audit committee with an insider.